A Description of The Future Orientation of Adolescent Online Gambling Addicts in The City of Palembang - Itryah Itryah; Aris Maulana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Adolescents are the next generation of young people who are expected to grow into moral individuals faster than the previous generation. The involvement of adolescents in online gambling will certainly have an impact on their development period, one of which is Future Orientation. Future Orientation is a representation of adolescents about the future that allows him to decide on goals, and assess how far these goals can be understood. This study aims to describe the future orientation of adolescent online gambling addicts. The subjects in this study were 2 people with the characteristics of online gambling addicts. This study uses a qualitative method with a phenomenological approach. Data collection techniques using interviews, observation, and documentation. Data validity uses Ecological Validity. Data reliability using the Audit Trail. The method of data analysis is to formulate verbatim copies of interviews and observations, search for categories, describe categories, and discuss research results. The results showed that both subjects had motivation, dreams, goals, efforts, plans, anticipations, and solutions for a future orientation toward education and work. In the future orientation toward the family, it is known that the two subjects also have motivation, dreams, goals, efforts, anticipations, and solutions. Still, the two subjects do not yet have a plan, and also the confidence to achieve them. So it can be concluded that the two subjects are more future-oriented towards education and work.Remaja merupakan generasi muda penerus bangsa yang diharapkan mereka akan tumbuh menjadi individu yang bermoral lebih cepat dari generasi sebelumnya. Terlibatnya remaja pada judi online tentunya akan berdampak pada masa perkembangannya, salah satunya yaitu Orientasi Masa Depan. Orientasi Masa Depan merupakan representasi remaja dalam kaitannya dengan masa depan yang memungkinkan dirinya untuk memutuskan tujuan, dan menilai sejauh apa tujuan tersebut dapat dipahami. Penelitian ini bertujuan untuk mengetahui gambaran orientasi masa depan pada remaja pecandu judi online. Subjek dalam penelitian ini berjumlah 2 orang dengan karakteristik pecandu judi online. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Validitas data menggunakan Ecological Validity. Reabilitas data menggunakan Audit Trail. Metode analisis data yakni memformulasikan salinan verbatim wawancara dan hasil observasi, mencari kategori, mendeskripsikan kategori dan membahas hasil penelitian. Hasil penelitian menunjukan bahwa kedua subjek memiliki motivasi, impian, tujuan, usaha, perencanaan, antisipasi dan solusi pada orientasi masa depan terhadap pendidikan dan pekerjaan. Pada orientasi masa depan terhadap keluarga, diketahui bahwa kedua subjek juga memiliki motivasi, impian, tujuan, usaha, antisipasi dan solusi, namun kedua subjek belum mempunyai perencanaan, dan juga keyakinan untuk mencapainya. Sehingga dapat disimpulkan bahwa kedua subjek lebih berorientasi masa depan terhadap pendidikan dan pekerjaan.